Board games as a tool for political education: Potential and limitations - Nikolai S. Skipin (RUDN Journal of Political Science, 2025)
The Game Studies subdiscipline still poorly examined the potential of board games in political education and their semantic and methodological limitations. The findings from the board game study can be extrapolated to digital gamification and business games but taking into account that each of these methods has its own characteristics. As examples, the concepts of Discussion à Visées Démocratique et Philosophique by the contemporary philosopher M. Tozzi and “philosophy for children” by M. Lipman are cited as tools for developing the education of a democratically oriented citizen. The game technologies are effective tools for political education of pupils and nurturing certain democratic values in them. However, the introduction of board games into the educational process is complicated by a number of limitations. Among the main problem areas are the following: simplification of the modelled processes for easy entry into the game; limitations related to game mechanics; complexity of creating game components and interface; assessment of the game’s effectiveness in the issue of political education. In order to effectively use the potential of gamification in political education, the author proposes to force the transition to the practical stage of formation of game methods in domestic education.